Changes in Physiology before, during, and after Yawning - Corey, Timothy P.; Shoup-Knox, Melanie L.; Gordis, Elana B.; Gallup, Gordon G. (Frontiers in Evolutionary Neuroscience, 2012)
The ultimate function of yawning continues to be debated. Here, we examine physiological measurements taken before, during, and after yawns in humans, in an attempt to identify key proximate mechanisms associated with this behavior. In two separate studies we measured changes in heart rate, lung volume, eye closure, skin conductance, ear pulse, respiratory sinus arrhythmia, and respiratory rate. Data were depicted from 75 seconds before and after yawns, and analyzed at baseline, during, and immediately following yawns. Patterns of physiological changes during yawning were then compared to data from non-yawning deep inhalations. Increases in heart rate, lung volume, and eye muscle tension were observed during or immediately following yawning. In one study, respiration period increased following the execution of a yawn. Much of the variance in physiology surrounding yawning was specific to the yawning event. This was not the case for deep inhalation. We consider our findings in light of various hypotheses about the function of yawning and conclude that they are most consistent with the brain cooling hypothesis.